PERALIHAN HAK MILIK ATAS TANAH BELUM BERSERTIPIKAT MELALUI JUAL BELI YANG BERKEPASTIAN HUKUM - Sukendah, Sukendah (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2021)
Land registration is to obtain collateral for land, while the status of land that is registered other than ownership rights is deemed inadequate because the time period is limited and there is a need for costs to extend the rights and therefore the validity of buying and selling ownership rights to land marked with evidence of land tax receipts is determined by fulfillment material requirements for land sellers and land buyers. The material requirement for land sellers is that the seller has the right and authority to sell ownership rights to the land, while the material requirement for land buyers is that the land buyer must fulfill the requirements as the subject of ownership rights to the land which is the object of buying and selling land. the research method is a normative juridical method, the results of research on the sale and purchase of ownership rights to land marked with evidence of land tax receipts with the intention of being registered (certified) at the district/city land office, then the sale and purchase of ownership rights to the land must be proven by the deed of the official making the deed authorized landlord (PPAT), buyers of land titles marked with evidence of land tax receipts who wish to register the land they have purchased are carried out through sporadic land registration that is individual (individual) or mass. the registration of the land is carried out by confirming the conversion (recognition of rights). Keywords: transfer of property rights, uncertified land, sale and purchase